A Comunicação Social do IBGE e as novas tecnologias para a integração da informação: o caso da introdução da Internet - Melo, Sandra Márcia de (2007)
The present essay tries to show the importance of the application of new information’s’ technology in the global world, especially the Internet, as indispensable tool in the improvement of the quality of the spreading of the studies produced for the Brazilian Institute of Geography and Statistics-IBGE, for the Coordination of Social Communication of the agency. The research was used administrative documents, such as Decrees, Resolutions, Bulletins of Service, material among others available that could assist in this Institutional memory. Specialized literature used as theoretical basement and for the qualitative research it applied the pertinent methodology to the research with collection of data of Verbal History. With the intention to rescue and to cover the historical way of the creation of the site of the IBGE in the Internet and the magnifying of its use for localities of Brazil, this term prioritized the importance that the Internet had for the spreading and dissemination of the works produced for the IBGE. To be able to analyze this process it was necessary to appeal to some concepts capable to help in the reflection on the transformations in course, such as: technological innovation, communicational culture, globalization, global identity, national identity, among others.